Using the SGDA Framework to Design and Evaluate Research Games. (June 2019) - Geerts, David; Nouwen, Marije; van Beek, Evert; Slegers, Karin; Chocron Miranda, Fernanda; Bleumers, Lizzy
Background. SeveralHCI researchers have started to use game design elements in their research to create playful methods for involving end-users indesign . Similar toserious games, suchresearch games serve a dual purpose: 1) to create an enjoyable experience for research participants, and 2) to collect user insights to inform the design process. Aim. We propose that theSerious Game Design Assessment (SGDA) Framework, that evaluates both a game's enjoyable purposes and its serious purposes, may be a valuable tool in assessing and developingresearch games . In this article, we apply theSGDA Framework to three existingresearch games, one involving train passengers in assessing potential future user experiences, one involving hospital staff in ideation for wearable technology, and one involving TV viewers in ideation for future video watching scenarios. Conclusion. Theassessment of thethree research games suggests that the framework is indeed applicable to research games and may, as such, provideHCI researchers with clear guidance when creating newresearch games .